Identification of Wolf-Dog Hybrids in Europe – An Overview of Genetic Studies - Dziech, Arkadiusz (Frontiers in Ecology and Evolution, 2021)
Significant development of genetic tools during the last decades provided opportunities for more detailed analyses and deeper understanding of species hybridization. New genetic markers allowed for reliable identification of admixed individuals deriving from recent hybridization events (a few generations) and those originating from crossings up to 19 generations back. Implementation of microsatellites (STRs) together with bayesian clustering provided abundant knowledge regarding presence of admixed individuals in numerous populations and helped understand the problematic nature of studying hybridization (i.a. defining a reliable thresholds for recognizing individuals as admixed or obtaining well grounded results representing actual proportion of hybrids in a population). Nevertheless, their utilization is limited to recent crossbreeding events. Single Nucleotide Polymorphisms (SNPs) proved to be more sensible tools for admixture analyses furnishing more reliable knowledge, especially for older generation backcrosses. Small sets of Ancestry Informative Markers (AIMs) of both types of markers were effective enough to implement in monitoring programmes, however SNPs seem to be more appropriate because of their ability to identify admixed individuals up to 3rd generations. The main aim of this review is to summarize abundant knowledge regarding identification of wolf - dog hybrids and discuss the most relevant problems relating to the issue, together with advantages and disadvantages of implemented markers and approaches.